Upaya Meningkatkan Volume Penjualan Pada Produk Madu Ternak P9 di Desa Parsanga - Fahrul Noerrahman; Miftahol Arifin (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
The problem examined in this thesis is because there is a problem in this research, in terms of market share of livestock honey, it is very difficult, the possibility of people still do not know the benefits or efficacy of honey itself and for natural honey, the target market is quite narrow, because the price is very high , but this natural honey has a long lasting period that can last for years. And also in the sale of livestock honey there are many problems when shipping far outside the city, because of every purchase there must be one cracked bottle in its packaging, and this is a problem that is being faced by P9 honey farmers in Parsanga Village. From the above analysis, researchers are interested to see how to increase sales volume. This makes the researcher raise the title Efforts to Increase Sales Volume on P9 Honey Products in ParsangaVillage. In answer these problem, researthers used descriptive qualitativ research. In this case, which is the focus of sales volume research, in this study researthers used a purposive sampling techniqu, consisting of key informants and supporting informants. The results of the study show that efforts to increase sales volumes affect the income of this livestock honey business, to achieve the target there must be steps that are passed or carried out in order to increase the sales volume of this livestock honey.